Transformations of the matrices of linear systems to their canonical form with desired eigenvalues - Kaczorek, Tadeusz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
A new approach to the transformations of the matrices of linear continuous-time systems to their canonical forms with desired eigenvalues is proposed. Conditions for the existence of solutions to the problems were given and illustrated by simple numerical examples.